Rastas on the road to healing: plant-human mobilities in Cape Town, South Africa - Reid, Andrew M (Social Anthropology, 2014)
Drawing on two months of deep ethnographic fieldwork consisting of informal conversations, recorded life history interviews, and participant observation, this dissertation employs a central theme of mobility to trace the processes through which individuals first come to engage with Rastafari and medicinal plants in Cape Town, South Africa, along with the movements through which they develop their knowledge and skill in relation to plant-medicines and healing. In doing so, the work develops an understanding of ganja (Cannabis sativa) as a catalytic link or connector between people, other medicinal plants, and transformation. Furthermore, plant-human assemblages are followed as they move across local and regional boundaries, with an examination of the implications these movements have for the health of people and ecosystems. On their transformational journeys, herbalists increase their plant knowledge, expand their secondary language capacity, learn to navigate multiple modes of transport, gain physical stamina and knowledge of the body, establish trade networks and build customer bases;; all of which contribute to the authority and healing abilities of an herbalist.